THE EVALUATION OF THE BRIGHT LITTLE MINDS CARING FOR GOODNESS PROJECT AT WATMOOKTHARA SCHOOL, NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Kaewkaemthong, Nutteera; Navakitpaiboon, Nilrat; Chatakan, Werayut (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims to assess the project system (System Assessment), project planning (Program Planning), project implementation (Program Implementation), project improvement (Program Improvement), and project certification (Program Certification) of the " The Evaluation of the Bright Little Minds Caring for Goodness Project at Watmookthara School Under Nakhon Si Thammarat Primary Educational Service Area Office 1" program. The sample group consisted of 205 participants, including 20 administrators and teachers, as well as 185 students and parents from Watmookthara School. The data collection tools comprised two parts. Part 1 included three sets of questionnaires: the first set focused on system assessment and program planning; the second set focused on program implementation and improvement; and the third set focused on program certification. Part 2 consisted of in-depth interview The research found that the assessment of the “The Evaluation of the Bright Little Minds Caring for Goodness Project at Watmookthara School Under Nakhon Si Thammarat Primary Educational Service Area Office 1” comprised five parts. Part 1: The assessment of the project system showed the highest level of appropriateness. Part 2: The assessment of project planning was also at the highest level of appropriateness. Part 3: The assessment of project implementation showed the highest level of appropriateness. Part 4: The assessment of project improvement suggested increasing the attractiveness of public relations, improving score recording through an online system to reduce teachers’ workload, ensuring fairness in scoring with clear rules, giving all students the opportunity to earn points, and expanding the project’s impact to families by allowing parents to participate for example, awarding points for helping with household chores. Part 5: The assessment of project certification indicated overall satisfaction that met all evaluation criteria.